EXAMEN ESPECIAL A LA CUENTA INVERSIONES EN BIENES DE LARGA DURACIÓN DE LA EMPRESA REGIONAL DE AGUA POTABLE ARENILLAS y HUAQUILLAS DURANTE EL AÑO 2013 - Vargas Jiménez, Kerly Guillermina (2016)
The work of qualification called "SPECIAL REVIEW ACCOUNT INVESTMENTS IN REAL LONG-TERM CORPORATE REGIONAL WATER ARENILLAS And HUAQUILLAS DURING 2013" was conducted with the aim of fulfilling a pre-qualification as Engineer requirement Accounting and Auditing, Public-Auditor Accountant at the National University of Loja and its development was executed in accordance with current laws, such as: General Regulations for the Administration and Control of durable goods, auditing standards generally accepted, and Internal Control Standards issued by the Comptroller General. For the implementation of the Special Examination proceeded to evaluate the internal control system in which irregularities were established with regard to: shopping, where breach with due process and the lack of development of an Annual Plan was determined Procurement; as well as the existence of incomplete inventories where there contains all the movable and immovable property; just as misclassification of Goods Production Administrative considered was evident; It executed in the physical findings determined that the records do not have the necessary features such as: brand, model number and color; the wrong maintenance also showed that the company gives to property; in terms of assets written off the existence of assets that should unsubscribe long ago observed; also records the proceedings do not have the signature or seal of legality; 5 the printed code applied to assets is found; existing balances depreciation in the audited financial statements verified; Finally seats reclassification product misregistration Capital Expenditures Long Life is developed. Based on these results, finally the Special Examination report, structured by the comment in describing the situation and inconsistencies found is made; the conclusions made based on the comments determining non-compliance with the Statement of Internal Control, General Regulations for the Administration and Control of durable goods; and the recommendations are directed to the responsible staff of the inconsistencies found.